Stratopheric greenhouse gas observation using a balloon-borne cryogenic sampler at Syowa Station, Antarctica - Satoshi Sugawara; Sakae Toyoda; Shigeyuki Ishidoya; Shinji Morimoto; Gen Hashida; Shuji Aoki; Takakiyo Nakazawa; Takashi Yamanouchi; Hideyuki Honda (National Institute of Polar Research, 2010)
Balloon-borne cryogenic samplers were launched from Japanese Antarctic Station, Syowa, on December 26, 2003 and January 5, 2004. Stratospheric air samples were successfully collected at 11 different altitudes from 10 to 30 km. After air samples were transported to Japan, they were analyzed for various greenhouse gases and their isotopes. The CO_2 concentration, thus obtained, shows no significant vertical gradient above 20 km. Secular increase of CO_2 concentration was clearly observable in the mid-stratosphere over Syowa station. From the average CO_2 concentrations in 1998 and 2004, the concentration difference was calculated to be 9.7 ppm, which is almost same the tropospheric trend. The average mean age was estimated to be 5.0±0.2 years above 20 km. This value was almost the same as that estimated from the CO_2 concentration data in 1998, 4.9±0.2 years. This result implies that there is no secular change of the mean age in the Antarctic stratosphere during this period. Vertical distributions of N_2O isotopomer ratios showed different characteristics among December, January, and previous observations in January 1998, showing that the short-term and long-term effects of transport processes.